RANCANG BANGUN SISTEM PENDINGIN UNTUK MESIN BUBUT BV 20 - Tampilang, Juvandi; Lumintang, Romels; Poeng, Rudy; Gede, I Nyoman (Fakultas Teknik Jurusan Teknik Mesin Universitas Sam Ratulangi, 2024)
The purpose of this study is to design and create a cooling system on the BV 20 lathe. The method used in this study is the design method by conducting direct design manufacturing based on the condition of the BV 20 lathe and designs by calculating the total head pump and pumping heading. The manufacturing process is carried out starting from the identification of working drawings and identification of components using existing tools or machines, ordering and procuring the market for other components. Then it can be produced a cooling system for a BV 20 lathe with a 3 watt pump. Keyword designs, cooling system, lathe BV 20